1988
DOI: 10.1007/bf02021649
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal examinations in the course of dietotherapy of mentally retarded obese in-patients

Abstract: Mentally retarded obese in-patients were fed by low-energy diet (4.2-4.6 MJ) for 9 months. During this period, an average of 13 +/- 4.5 kg loss of body mass occurred in men and 16 +/- 2.7 kg in women. Anthropometric measurements were performed before starting the dietotherapy and in the ninth month. Changes of body fat could be followed well when calculated according to BMI. Less reliable results were obtained with skinfold thickness measurements, presumably due to body deformities. Results of clinical laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The interventions did not report using behaviour change strategies or advising on appropriate physical activity interventions to assist weight loss (see Table 3) [21,22]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interventions did not report using behaviour change strategies or advising on appropriate physical activity interventions to assist weight loss (see Table 3) [21,22]. …”
Section: Resultsmentioning
confidence: 99%
“…The intervention in Antal et al [21] took place in an institution but no information was reported regarding the profession of the people who delivered the intervention. Bertoli et al [22] reported that the intervention was delivered by a medical practitioner and a dietitian in the community.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations